Маркетинговые проблемы промышленных предприятий - Верховцева, О. Н. (My University, 2014)
В работе произведено практическое исследование маркетинговых проблем на промышленных предприятиях химической отрасли города Тольятти. Также разработаны рекомендации и сделаны выводы по эффективности их внедрения.

This paper made a case study of marketing problems at the industrial enterprises of the chemical industry of the city of Togliatti. Also developed recommendations and conclusions on the effectiveness of their implementation.
Marketing problems of industrial enterprises
Keywords: стратегический маркетинг; анализ деятельности предприятия; маркетинговые проблемы; промышленный маркетинг; strategic marketing analysis of the company; marketing problems; industrial marketing